Measuring customer-based brand equity: Empirical evidence from the sportswear market in China - Tong, Xiao; Hawley, Jana M. (My University, 2009)
This study seeks to examine the practicality and applications of a customer-based brand equity model in the Chinese sportswear market. Design/methodology/approach - Based on Aaker’s well-known conceptual framework of brand equity, this study employed structural equation modeling to investigate the causal relationships among the four dimensions of brand equity and overall brand equity in the sportswear industry. The present study used a sample of 304 actual consumers from China’s two largest cities, Beijing and Shanghai. Findings - The findings conclude that brand association and brand loyalty are influential dimensions of brand equity. Weak support was found for the perceived quality and brand awareness dimensions. Research limitations/implications - Future research needs to be done if the results are to be expanded into other regional Chinese markets in light of the significant gaps between different regions. Further research also could strengthen this analysis by adding performance measurement into the model. Practical implications - The paper shows that sportswear brand managers and marketing planners should consider the relative importance of brand equity in their overall brand equity evaluation, and should concentrate their efforts primarily on building brand loyalty and image. Originality/value - This study contributes to the scant literature testing the applicability of consumer-based brand equity in the sportswear industry. Since China is the world’s fastest-growing market for sportswear products, this study also provides important insights about the understanding of Chinese consumers’ perceptions of overall brand equity and its dimensions.
Keywords: Brand equity; Clothing; China; Consumers; Sportswear